2018
DOI: 10.18805/ijar.b-878
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol levels in Hair goats of Aksaray Region

Abstract: This study was conducted to determine the levels of serum total cholesterol in Hair goats in different gender and age ranges. For this purpose, the blood samples from 120 Hair goats, young (£ 6 months) and adult (2-4 years), which were found to be clinically healthy, were taken from the vena jugularis. Triglyceride, total cholesterol, HDL and LDL cholesterol levels were measured in sera samples. The mean values in adult female goats, young female goats, adult male goats and young male goats were found. Triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Higher concentrations of total cholesterol, HDL cholesterol and VLDL cholesterol in the blood of older goats were observed compared to group I. A similar trend for blood cholesterol concentrations was determined in Marwari goats from India (Pandey and Sareen, 2007) and in Hair goats from Turkey (Karaşahin et al, 2018). Very few studies are available regarding NEFA concentrations within goats' blood.…”
Section: Discussionsupporting
confidence: 63%
“…Higher concentrations of total cholesterol, HDL cholesterol and VLDL cholesterol in the blood of older goats were observed compared to group I. A similar trend for blood cholesterol concentrations was determined in Marwari goats from India (Pandey and Sareen, 2007) and in Hair goats from Turkey (Karaşahin et al, 2018). Very few studies are available regarding NEFA concentrations within goats' blood.…”
Section: Discussionsupporting
confidence: 63%
“…KIRAN et al (2012) determined a similar trend for blood cholesterol concentration in goats from Pakistan, although without significant differences between different age groups of goats. On the contrary, KARAŞAHIN et al (2018) determined the opposite trend in cholesterol concentrations in female Hair goats in Turkey. In the research by NAZIFI et al (2002) conducted on Iranian male goats, the significant effect of age was determined on the concentrations of triglycerides and VLDLcholesterol in serum, with values being lower in older animals.…”
Section: Discussionmentioning
confidence: 91%
“…The overall mean tCho, TG, and VLDL Cho ranges calculated in this study are in accordance with physiological ranges reported for clinically healthy nonpregnant goats (tCho: 53.9 ± 1.59 mg/dL), pregnant goats (tCho: 82.08 ± 1.58 mg/dL, TG: 85–100 mg/dL, and VLDL Cho: 17–20 mg/dL), and adult female goats (2–4 years) (tCho: 113.64 ± 23.03 mg/dL) [ 19 , 20 , 21 , 64 , 65 ], and confirm the significant increase of serum tCho, TG, and VLDL Cho concentrations in small ruminants, from the last gestational phase, peaking at 115 and 135 days, compared to the early and mild gestational period [ 19 ]. Likewise, the increased serum tCho, TG, and VLDL Cho concentrations in pregnant goats are in accordance with data observed in small ruminants, in which this increase was attributed to an increased hepatic TG synthesis [ 10 , 19 , 21 , 66 ].…”
Section: Discussionmentioning
confidence: 99%